Supply response of selected crops in Bangladesh - Mia, Mohammad Ismail (2012)
Bangladesh is one of the most populous countries in the southern part of Asia with a population density of 1074 person per square kilometre. Agriculture contributes about 21% to the country’s GDP and employs over 48% of the total labour force in 2010. Jute, sugarcane, lentil and mustard are important crops. Jute and sugarcane are cash crops. Lentil is a popular pulse crop considered as poor man’s protein. Mustard is an oil crop. Area and production of all these are declining while their imports, poverty and unemployment are in rise. The objective of this study is (i) to determine the growth rates of area and production of jute, lentil, mustard and sugarcane; (ii) to estimate the supply responsiveness of these crops to change in price and non price factors; and (iii) to compare the acreage response of these four crops. The study utilised a simple calculation of growth rate on margin residuals such as area and production and also estimates acreage responsiveness of these crops to change in price and non price factors use of Johansen cointegration aopproach and vector error correction model (VECM) using data 1980/81-2007/08. Area growth rates of jute were negative for all the sub periods as well as for the whole period. Jute production also grew negatively. Lentil area grew negatively while its production grew positively. Growth rates of both area and production of mustard and sugarcane were negative during the last 28 years period. The short-run elasticity of jute acreage is 0.5463 while in the long-run it is 1.2941. Jute growers make considerable area adjustments in the short-run and long-run in response to its own price. Coefficient of aus price was negative. Weather appeared to have positively influenced jute acreage. Short-run and long-run acreage elasticity of lentil with respect to its price is 0.2296 and 0.3628 respectively suggesting that lentil growers do not make considerable area adjustments in response to price of the crop. Weather variable did not appear to have shown any influence on lentil area in the short-run. The short-run and long-run elasticities of area with respect to mustard price is 0.2403 while in the long-run, the real mustard price elasticity is 0.6398. In terms of sugarcane, the short-run and longrun elasticities of sugarcane area with respect to its real price are 0.1990 and 0.6731 respectively. Low short-run and long-run elasticities of these crops trend to make minimum area adjustment in response to their expected prices. The study simples that the area allocation decision of the farmers does not only depend on price of the product, a set of other factors such as improved technology,ensuring input delivery, providing support price, providing extension services and preventing force to artificially control prices are also necessary. Hence, in a land scarce country like Bangladesh, a comprehensive set of policy is required to provide economic incentives that will induce producers and other industry participants to invest above on the said sectors.